A COMPARATIVE STUDY ON THE EFFECT OF STUDENTS RELATED FACTORS (SELF–CONFIDENCE, ATTITUDE AND FAMILY BACKGROUND) ON SCIENCE ACHIEVEMENT OF MALAYSIAN & SINGAPOREAN STUDENTS (Sains Humanika, 2010)
This study is a cross–national comparative study to assess the effects of student related factor (students’ self–confidence in learning science, attitude toward science, family background and being safe in school) on science achievement of students of Malaysia and Singapore. A total of 5314 eighth–grade students (3071 girls and 2243 boys) from Malaysia and 6018 students (2938 girls and 3080 boys) from Singapore who participated in Trends in International Mathematics and Science Study (TIMSS) 2003 were studied. The Principal Component Analysis (PCA) was performed to examine the underlying constructs among the Students’ Questionnaire items. Subsequently, Multiple Regression technique was employed to explain the variance of science achievement. The results of (PCA) showed 23 items from the questionnaire distributed among six factors for both sets of the data. The results of (PCA) showed 23 items from the questionnaire distributed among six factors for both sets of the data. The regression results revealed that 26% of the variance of science achievement of Malaysian students were accounted for by the selected factors. In addition, 33% of the variance of science achievement of Singaporean contributed by the selected factors.
Keywords: Achievement; attitude; factors; family background; self-confidence; science; TIMSS